Inspección visual de afectaciones y daños en el pavimento rígido de la vía calle 81 sur entre carrera 14 hasta carrera 5 del barrio gran Yomasa localidad de Usme (2022)
This document aims to show the current state of the 13 sections or road segments that make up the road corridor 81 South Street between Carrera 14 to Carrera 5 by visual inspection of the pathologies present in the pavement slabs following the visual inspection manual for rigid pavement of INVIAS and determine the technical diagnosis for the recommended intervention according to the calculation of the pavement condition index and classification of the Instituto de Desarrollo Urbano IDU; is the main road of the Gran Yomasa neighborhood which connects the Bolonia, Curubo, Compostela and Betania neighborhoods with Caracas Avenue, on the road is the Parroquia San Atanasio and the school I. E.D. Federico García Lorca, it has a great economic and social activity which makes this road very busy for private vehicles, pedestrians and public transport vehicles; it has stops for five SITP routes and two feeder bus routes of Transmilenio